Population Potential as a Modulator of Land use Changes in Poland’S Metropolitan Areas - Werner, Piotr; Korcelli, Piotr; Kozubek, Elżbieta (Quaestiones Geographicae, 2014)
Land use is defined as a spatial distribution of individual forms of land cover patches, utilised or not utilised by humans within the framework of mutual and spatial relationships. It refers to the functional character of a given terrain, and is also identified with a socio-economic description of the land surface. Changes in land use can be interpreted as a complex and, to some extent, a random process. These assumptions serve as a point of departure in an attempt to evaluate spatial and temporal differences in land use changes in the metropolitan areas of Poland, using the entropy formula. The analysis focuses on population development as a factor that impacts upon land use change. The approach proposed here allows us to study land use dynamics in detail, with the help of cartographic visualisation.